PENGARUH MODEL PROJECT BASED LEARNING TERHADAP KETERAMPILAN BERPIKIR KREATIF DAN KOLABORATIF MATA PELAJARAN IPAS PADA PESERTA DIDIK KELAS IV DI MADRASAH IBTIDAIYAH - Nurhayati, Emy; Sunardi; Prastiti, Tri Dyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the effect of the Project Based Learning (PjBL) model on the creative and collaborative thinking skills of fourth-grade students in the subject of Natural and Social Sciences (IPAS) at Madrasah Ibtidaiyah. The research employed a quasi-experimental method with a nonequivalent control group design. The subjects consisted of an experimental group taught using the PjBL model and a control group taught using conventional methods.The results show that there was a difference in the improvement of creative thinking skills between the experimental and control groups; however, the t-test indicated that this difference was not statistically significant (t = -1.192, df = 38, p = 0.241). This means that the application of the PjBL model did not significantly affect the enhancement of creative thinking skills. In contrast, for collaborative skills, the t-test revealed a statistically significant difference between the two groups (t = -5.766, df = 38, p < 0.001), with a mean difference of 10.82500, indicating that the PjBL model had a positive effect on students’ collaboration skills. Furthermore, the F-test showed that the calculated F value was greater than the F table value (17.156 > 3.592) with a p-value < α (0.000 < 0.050), leading to the rejection of H0. This indicates that, simultaneously, the PjBL model significantly influenced both creative and collaborative thinking skills.